2008
DOI: 10.1111/j.1945-5100.2008.tb00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of shock remanent magnetization for demagnetized samples in a weak magnetic field (7 μT) by shock pressures 5–20 GPa without plasma‐induced magnetization

Abstract: Abstract-Demagnetized samples of cobalt precipitates in a copper matrix were shocked to 5, 10, and 20 GPa in a weak magnetic field of 7.7 µT to elucidate the origins of the natural remanent magnetization of meteorites and the magnetic anomalies of impact craters on the moon and Mars. The samples placed in the target acquired shock remanent magnetization (SRM) whose intensity increased up to 21.3 times compared with the demagnetized state, but SRM intensity and shock intensity were not correlated. The SRM direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…These properties mean that SRM acquired at pressures lower than 5 GPa can be considered as a reliable source of information about paleofields at the moment of impact, for direction but also for intensity provided proper calibration is achieved. For pressures higher than~5 GPa however, shock waves can permanently modify the intrinsic magnetic properties of rocks (Gattacceca et al, 2007;Gilder and Le Goff, 2008;Louzada et al, 2010) and the SRM direction may be linked to the shock direction (Funaki and Syono, 2008).…”
Section: Shock Magnetization Of Lunar Materials: State-of-the-artmentioning
confidence: 99%
“…These properties mean that SRM acquired at pressures lower than 5 GPa can be considered as a reliable source of information about paleofields at the moment of impact, for direction but also for intensity provided proper calibration is achieved. For pressures higher than~5 GPa however, shock waves can permanently modify the intrinsic magnetic properties of rocks (Gattacceca et al, 2007;Gilder and Le Goff, 2008;Louzada et al, 2010) and the SRM direction may be linked to the shock direction (Funaki and Syono, 2008).…”
Section: Shock Magnetization Of Lunar Materials: State-of-the-artmentioning
confidence: 99%
“…In addition to our previous work (Gattacceca et al, 2008), we provide here additional information about SRM directional homogeneity. Indeed, there has been some debate about whether small-scale heterogeneities could exists, due to, for instance, to local transient magnetic fields during shock wave propagation or other hypothesized effects Schultz, 1988, 1999;Soloviev and Sweeney, 2005;Funaki and Syono, 2008). To study the homogeneity of SRM acquisition, an additional basalt sample was AF demagnetized and imparted with an SRM using a 1.9 GW•cm -2 laser flux.…”
Section: Shock Magnetizationmentioning
confidence: 99%
“…Shock magnetization, i.e. the acquisition of new remanence by shock in the presence of a magnetic field, has received much less attention (Nagata, 1971;Pohl et al, 1975;Pohl et al, 1981, Nagata et al, 1983Gattacceca et al, 2008;Funaki and Syono, 2008) in part because it is experimentally more demanding as it requires ambient field control during the shock experiments. Yet, the fundamental properties of shock remanent magnetization (SRM, defined by Nagata, 1971) are now well established (Pohl et al, 1975;Gattacceca et al, 2008): SRM is proportional to the ambient field in the low-field (< ~1 mT) limit and is strictly parallel to the ambient magnetic field for magnetically isotropic rocks; its intensity is independent of the angle between the shock wave propagation direction and the ambient field for isotropic rocks, it can have a significant intensity compared to thermoremanent magnetization (TRM) acquired in the same ambient field (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…If an external magnetic field does not exist at the time of the shock event, any stable NRM may be absent due to shock demagnetization. In contrast, Funaki and Syono (2008) demonstrated that the scattered directions of remanent magnetization resulting from shock remagnetization in the external magnetic field of 7 µT are characteristic of shocks between 5 and 20 GPa. Therefore, analyses of the shock demagnetization and remagnetization processes of Martian meteorites are of major importance in understanding the results of paleomagnetic studies.…”
Section: Estimation Of the Magnetic Field On Marsmentioning
confidence: 92%